The Impact of Community-Driven Development Program on Rural Households Economic Well-being: Evidence from Village Funds - Sutisna, Alan; Qibthiyyah, Riatu Mariatul (Fakultas Ekonomi Universitas Samudra, 2023)
Indonesia has implemented the concept of community-driven development in rural areas through village funds since 2015. Village funds are one of the instruments to minimize the impact of Covid-19 in rural areas. This research was conducted to provide an overview of the impact evaluation of village funds on the economic well-being of rural communities in each household quantile. This study uses data on the characteristics of 35,759 households obtained from merging results of the March & September 2020 Susenas data with the village fund data in each district/city area. Data were analyzed using smoothed instrumental variables quantile regression, which overcame endogeneity issues and produced robust estimates. The study results show that the village fund has a positive and significant impact on the economic well-being of rural households. Still, their impact is felt more by the upper middle class and households in the Sumatra region.